Implementasi Pembangunan Desa Melalui Integrasi Nilai Kearifan Lokal Berbasis Pendekatan Partisipatif - Rini Novianti; Khomsahrial Romli; M. Mawardi J; Sri Ilham Nasution (Journal Of Business, Finance, and Economics (JBFE), 2025)
Village development requires an approach that adapts to the social, cultural, and economic characteristics of the local community. This study examines how the